OP56 Do early life exposures explain why more advantaged children get eczema? findings from the UK millennium cohort study. (31st August 2015) - Taylor-Robinson, DC; Williams, H; Pearce, A; Law, C; Hope, S
Abstract : Background: Atopic dermatitis (eczema) is one of the most common conditions of childhood, and can have a serious effect on children's and families' quality of life. Previous studies have suggested that childhood eczema is socially patterned, with higher incidence in more advantaged populations, but it is unclear what explains these differences. We therefore explored the epidemiology and risk factors for eczema, in a contemporary UK birth cohort, with a focus on socio-economic circumstances and the extent to which any socio-economic gradient might be explained by other early-life risk factors for eczema. Methods: Longitudinal analysis of the United Kingdom Millennium Cohort Study (MCS), based on 14, 499 who participated in sweeps of the study at ages 9 months and 5 years. At 5 years mothers were asked about whether their child has "ever had eczema". Odds ratios (OR) and 95% confidence intervals (CI) for eczema were estimated using logistic regression, according to maternal education. Maternal, antenatal and early life characteristics were explored to assess if they explained the associations found between maternal education and eczema. Results: 35.1% of children had ever had eczema by age five. Children of mothers with degree level qualifications were more likely to have eczema compared to children of mothers with no educational qualifications (OR 1.52 95% CI 1.31–1.76) and there was a clear gradient across the socioeconomic spectrum. Maternal atopy, breastfeeding (1–6 weeks and 6 months or more), introduction of solids under 4 months or cow's milk under 9 months, antibiotic exposure in the first year of life and "grime" exposure were independently associated with an increased risk of eczema. Female sex, Pakistani and Bangladeshi ethnicity, smoking during pregnancy and exposure to environmental tobacco smoke (ETS) and other siblings were independently associated with a reduced risk for eczema. When these factors were entered into the main model, the OR for eczema in children whose mothers had a degree reduced to 1.26 (95% CI 1.03 to 1.5). Conclusion: In this representative UK cohort, there was a significant excess of childhood eczema reported in more advantaged  children and this was attenuated when accounting for maternal, antenatal and early life factors.